Use of Verbal Language in Private Teaching of English for Children Age 6 – 7 Years - Atma Jonar Asih; Ulpah Maisari; Ridwan Syahputra; Sri Dharmawati (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2021)
This study concerns investigates the value of the use Verbal communication is the use of words to share information with other people. It can therefore include both spoken and written communication. However, many people use the term to describe only spoken communication. The verbal element of communication is all about the words that you choose, and how they are heard and interpreted. The purpose of this research is to Encouraging a child to use verbal communication is an important step in their overall development and it is important that you open them up to as many different voices and words as possible, in order to help them grow. The people they have around them in terms their childcare are ideal for helping to develop communication skills. Playing games, encouraging conversation, and simple naming activities are all fantastic tools which can encourage verbal communication back and forth.